Model in Chemistry Education and Theoretical Foundations for the Presentation of Information Models in Chemistry - Jobborov Farhod Buriyevich (Genius Publishing Group, 2022)
The article presents the following in models of symbolic chemical training: demonstration; structure and consistency; durability; scientific; the importance of the principles of connection between theory and practice has been analyzed.
Keywords: Educational; symbol; model; didactic